Floristic composition and structure of the tree component and environmental analysis of a fragment of a highland araucaria forest in the municipality of Painel, Santa Catarina state Florística e estrutura do componente arbóreo e análise ambiental de um fragmento de floresta ombrófila mista alto-montana no Município de Painel, SC - Higuchi, Pedro (2013)
The highland Araucaria Forest is a little-studied forest formation, occurring in altitudes above 1,000 m. The objectives of this study were to understand the structural and floristic patterns of the tree component of a remaining of this forest in the southern plateau region of Santa Catarina State and to determine the environmental variables that influence these patterns. The tree component survey and the environmental data collection were conducted in 50 plots of 200 m2. Within these plots, all living trees with circumference at breast height (CBH) ≥ 15,7 cm were measured (CBH and height) and identified. In each plot, environmental variables related to soils physical and chemical traits, topography and canopy cover were collected. Phytosociological parameters and the diameter structure (whole tree community and tree populations with the importance value above 5 %) were calculated. The floristic-structural similarities among plots were analyzed by NMDS (Nonmetric Multidimensional Scaling) and vectors of environmental variables (p < 0.05) were plotted a posteriori. A total of 50 tree species were identified, distributed in 33 genera and 20 families. The species with the highest VI were Araucaria angustifolia (Bertol.) Kuntze (17.32 %), Myrceugenia euosma (O. Berg) D. Legrand (15.24 %) and Acca sellowiana (O. Berg) Burret (7.84)The diameter structure of the whole community and of the study populations (except Dicksonia sellowiana Hook.) showed a distribution close to the "inverted J". The NMDS analysis showed a higher percentage of clay in the plots with the highest density of Acca sellowiana and lowest percentage in the plots with high density of Dicksonia sellowiana, Inga lentiscifolia Benth. and Ocotea pulchella Mart. Plots with higher declivity had a higher density of Drimys brasiliensis Miers and those of lower declivity, higher elevation and greater canopy closure, had a higher occurrence of Drimys angustifolia Miers, Prunus myrtifolia (L.) Urb, Calyptranthes concinna DC. and Myrceugenia oxysepala (Burret) D. Legrand & Kausel.